IMMU-02. TARGETING CD200 ACTIVATION RECEPTORS TO OVERCOME THE IMMUNOSUPPRESSIVE TUMOR MICROENVIRONMENT: A NEW DIRECTION FOR CHECKPOINT IMMUNOTHERAPY. (31st May 2017) - Ampudia-Mesias, Elisabet; Moertel, Christopher; Olin, Michael
Abstract: Glioblastoma multiforme is an incurable primary brain tumor. The standard of care consists of resection followed by radiation and chemotherapy is associated with a median overall survival of 14.6 months. To address this dismal outcome, aggressive interventions need to be pursued. Recently, the FDA approved immune checkpoint inhibitor therapy for solid tumors that are otherwise refractory to standard therapy heralding a new era for effectively treating cancer. Yet, immune checkpoint inhibitors yield poor responses for patients with glioblastoma, calling into question whether cancer immunotherapy can be applied to glioblastoma. We have recently reported that inhibiting an alternative immune checkpoint, CD200, inhibits tumor-induced immunosuppression without toxic side effects. CD200 protein suppresses immune activation after engaging the CD200 inhibitory receptor, which is restricted to immune cells. Recently, our laboratory reported that CD200 inhibits brain tumor immunity via three separate mechanisms: 1) CD200 is secreted from brain tumors into the cervical lymph nodes where it induces an immunosuppressive environment, 2) CD200 is upregulated in GBM-associated vascular endothelial cells, tolerizing CD200R + lymphocytes, and 3) CD200 within tumor-derived vaccines suppresses an antitumor response. To combat the suppressive mechanisms of CD200, we are targeting activation receptors to override the suppressive signal of the CD200 checkpoint blockade. Targeting these receptors activate antigen presenting cells enhancing dendritic cell maturation, cytokine production and antigen specific T cell activation, which significantly extend survival in two murine glioma models. In addition, in an ongoing clinical trial using dogs diagnosed with high-grade glioma, patients receiving a canine specific CD200 peptide inhibitor in combination with the autologous tumor lysate vaccine had enhanced survival up to 467 days, relative to 214 days with lysate alone, without any observed toxicity or signs of reoccurrence. Importantly, we developed human CD200 inhibitors demonstrating strong immune responses with the goal of a Phase I trial early 2018.